Przestrzeganie wybranych elementów zwykłej dobrej praktyki rolniczej w gospodarstwach rolnych w Kotlinie Kargowsklej na przykładzie gminy Bojadła (obszar ONW) i Trzebiechów posiadających min. 2DJP = Application of chosen elements of good agriculture practice in Kargowa Valley exampled by over 2DJP farms in parishes Bojadła (ONW area) an Trzebiechów - Kozieja, Wojciech; Gniazdowski, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
It is becoming a popular opinion that agriculture bears particular responsibility for protection of the environment. Agriculture covers circa 60% of the country area and through the processes of production it influences seriously the quality of water, soil and air as well as the changes in biological heterogencity of the environment.
Keywords: 3 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zrównoważona gospodarka zasobami naturalnymi" (24-25.06.2004)